Observation of the doubly Cabibbo-suppressed decay Ξ c + → pϕ - The LHCb collaboration; R. Aaij; C. Abellán Beteta; B. Adeva; M. Adinolfi; C. A. Aidala; Z. Ajaltouni; S. Akar; P. Albicocco; J. Albrecht; F. Alessio; M. Alexander; et al. (Journal of High Energy Physics, 2019)
Abstract The doubly Cabibbo-suppressed decay Ξ c + → pϕ with ϕ → K + K − is observed for the first time, with a statistical significance of more than fifteen standard deviations. The data sample used in this analysis corresponds to an integrated luminosity of 2 fb−1 recorded with the LHCb detector in pp collisions at a centre-of-mass energy of 8 TeV. The ratio of branching fractions between the decay Ξ c + → pϕ and the singly Cabibbo-suppressed decay Ξ c + → pK − π + is measured to be ℬ Ξ c + → p ϕ ℬ Ξ c + → p K − π + = 19.8 ± 0.7 ± 0.9 ± 0.2 × 10 − 3 , $$ \frac{\mathrm{\mathcal{B}}\left({\varXi}_c^{+}→ pφ \right)}{\mathrm{\mathcal{B}}\left({\varXi}_c^{+}→ pK^{-}{π}^{+}\right)}=\left(19.8± 0.7± 0.9± 0.2\right)× {10}^{-3}, $$ where the first uncertainty is statistical, the second systematic and the third due to the knowledge of the ϕ → K + K − branching fraction.